Hindlimb Immobilization Increases IL-1β and Cdkn2a Expression in Skeletal Muscle Fibro-Adipogenic Progenitor Cells: A Link Between Senescence and Muscle Disuse Atrophy - Parker, Emily; Khayrullin, Andrew; Kent, Andrew; Mendhe, Bharati; Youssef El Baradie, Khairat Bahgat; Yu, Kanglun; Pihkala, Jeanene; Liu, Yutao; McGee-Lawrence, Meghan; Johnson, Maribeth; Chen, Jie; Hamrick, Mark (Frontiers in Cell and Developmental Biology, 2022)
Loss of muscle mass and strength contributes to decreased independence and an increased risk for morbidity and mortality. A better understanding of the cellular and molecular mechanisms underlying muscle atrophy therefore has significant clinical and therapeutic implications. Fibro-adipogenic progenitors (FAPs) are a skeletal muscle resident stem cell population that have recently been shown to play vital roles in muscle regeneration and muscle hypertrophy; however, the role that these cells play in muscle disuse atrophy is not well understood. We investigated the role of FAPs in disuse atrophy in vivo utilizing a two-week single hindlimb immobilization model. RNA-seq was performed on FAPs isolated from the immobilized and non-immobilized limb. The RNAseq data show that IL-1β is significantly upregulated in FAPs following two weeks of immobilization, which we confirmed using droplet-digital PCR (ddPCR). We further validated the RNA-seq and ddPCR data from muscle in situ using RNAscope technology. IL-1β is recognized as a key component of the senescence-associated secretory phenotype, or SASP. We then tested the hypothesis that FAPs from the immobilized limb would show elevated senescence measured by cyclin-dependent kinase inhibitor 2A (Cdkn2a) expression as a senescence marker. The ddPCR and RNAscope data both revealed increased Cdkn2a expression in FAPs with immobilization. These data suggest that the gene expression profile of FAPs is significantly altered with disuse, and that disuse itself may drive senescence in FAPs further contributing to muscle atrophy.